(untitled) (Al-Qamar, 2024)
The Holy Quran is last divine book of righteousness for mankind. Allah Almighty has himself ensured its security and sanctity. This article also discusses about the contributions of Imam Abdul Karim Bin Hawasn Qushari in the field of Tassawwuf. This article is about Tassawwuf and Sufism and it tells us about nature and evolution of Sufism. Some orientalists endeavored always to make objections and allegations on Tassawwuf and its source. They tried to prove that Sufism does not belong to Islam. The capital sources of the Tassawwuf and Sufism are the Holy Quran and Sunnah of the Holy Prophet (صلی اللہ علیہ وآلہ وسلم). This article explains that the real source of Tassawwuf is verses of Holy Quran and traditions of the Holy Prophet (صلی اللہ علیہ وآلہ وسلم). Tassawwuf has been also narrated in this article. Examples of Tassawwuf have been given from Quran and Hadith. Opinion of Sufi masters has been included. Important Books written about Tassawwuf have also been discussed briefly. Many other Sufism writers’ opinion have also been written in this topic. The sources of Tassawwuf remain the topic of criticism and discussion among the Islamic and non-Islamic critic. The orientalists stated that the Tassawwuf is dependent in its existence to the Christianity and other religions, but the argument and justifications of critic in this regard are baseless and reasonless.